2017
DOI: 10.5812/ccn.12042
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Critical Care Nurses’ Information Literacy Through an Evidence-Based Practice Workshop: A Quasi-Experimental Study

Abstract: Background: Advanced nursing practice necessitates using research findings and evidence as well as effective clinical decision making. The use of evidence in nursing practice is not only a duty, but also a professional responsibility and practice. Objectives: The current study aimed at assessing the effects of an evidence-based practice training workshop on the information literacy of critical care nurses. Methods: The current 2-group, pretest-posttest, quasi-experimental study was conducted in 2016. A conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…were better prepared and con dent to use the electronic health record (EHR), make better clinical decisions and provide better patient care. The nurse educators also better mastered EBP and used nursing process models in their work [28] Iranian studies also reported a signi cant increase in NI competency of the faculty members [44] and nurses in ICUs after attending the educational program compared with the control group [17]. Similar results may be due to application of a similar training program and advancement of HIT in clinical setting and everyday life, which has prompted individuals and nurses to acquire and enhance their NI competency.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…were better prepared and con dent to use the electronic health record (EHR), make better clinical decisions and provide better patient care. The nurse educators also better mastered EBP and used nursing process models in their work [28] Iranian studies also reported a signi cant increase in NI competency of the faculty members [44] and nurses in ICUs after attending the educational program compared with the control group [17]. Similar results may be due to application of a similar training program and advancement of HIT in clinical setting and everyday life, which has prompted individuals and nurses to acquire and enhance their NI competency.…”
Section: Discussionmentioning
confidence: 89%
“…Haseli [44] showed that the scores of NI competency in the control group did not have a signi cant difference before and after the educational course. Esfandani et al investigated critical care nurses and reported that the scores of information seeking skills were low in the control group with no signi cant difference in their scores before and after the intervention [17]. Conversely, a study also reported that the posttest score of information skills increased in the control group [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these developments, nurses must embrace innovation and use their abilities and knowledge to change and develop their old ways of thinking [10]. They are also required to actively participate in designing and deploying IT in health care [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…So, the need for IT-qualified nurses is felt at a high level more than ever [14]. Critical care nurses' need for IT competency is much higher than those of other nursing groups due to the increased sensitivity of working in critical care units, critical and high-risk situations of patients, and application of sophisticated high-tech equipment [12].…”
Section: Introductionmentioning
confidence: 99%